Permanganate Oxidation of Microcystin-LA: Kinetics, Quantification, and Implications for Effective Drinking Water Treatment. (28th May 2019) - Szlag, David C.; Spies, Brian; Szlag, Regina G.; Westrick, Judy A.
Abstract : Permanganate pretreatment of drinking water is effective in transforming dissolved, noxious contaminants and in reducing halogenated by-products. Permanganate targets specific compounds such as taste and odor compounds, disinfection precursors, manganese, and natural organic contaminants that are not removed readily by conventional treatment alone. Cyanobacterial blooms (cHABs) can increase disinfection by-product precursors as well as the cyanotoxin, microcystin (MC), a potent liver toxin. MC toxicity is conferred by a unique, conserved amino acid, Adda, that inhibits protein phosphatase 1 and 2A. Although over 150 MC congeners have been reported, thousands of MCs are statistically possible. Over the last ten years, one congener, MC-LA, has been reported with increasing frequency, making it one of the most common cyanotoxins identified in North American freshwater systems; yet its oxidation has not been widely studied. Frequently, Adda specific enzyme-linked immunosorbent assay (ELISA) and protein phosphatase inhibition assay (PPIA) are used to quantitate total MCs to evaluate treatment efficiency and exposure. Anecdotal reports suggest that MC degradation products can cause interference with the Adda-ELISA. MC-LA was used as the model MC compound in this study. PPIA quantitation of MC-LA in water agreed with liquid chromatography high resolution mass spectrometry (LC/HRMS), whereas the ELISA quantitation did not agree with LC/HRMS quantitation. We determined the second order rate constant for MC-LA as 118 ± 9 M −1 s −1, the activation energy to be 21.2 kJ mol −1, and the rate to be independent of pH between pH 6 and 9. Ten oxidation products (OPs) were observed by LC/HRMS and three primary reaction pathways are proposed. The reaction pathways were used to explain differences in the quantification by Adda-ELISA, HRMS, and PPIA. The oxohydroxylation of MC-LA produced two major OPs, C46 H67 N7 O14 [M+H] + = 942.4819 and C46 H69 N7 O15 [M+H] + =960.4925. Major OPs may contain an unmodified Adda and are the likely cause of interference with the Adda-ELISA. Several governmental agencies recommend the use of the Adda-ELISA to determine the MC quantitation for treatment efficiency and customer exposure; yet our results suggest that these or other OPs interfere with the Adda-ELISA causing artificially high values for total MCs.